Adaptive radiation therapy strategies in the treatment of prostate cancer patients using hypofractionated VMAT. Issue 12 (16th November 2021) - Siciarz, Pawel; McCurdy, Boyd; Hanumanthappa, Nikesh; Van Uytven, Eric
Abstract: Purpose: To perform a comprehensive evaluation of eight adaptive radiation therapy strategies in the treatment of prostate cancer patients who underwent hypofractionated volumetric modulated arc therapy (VMAT) treatment. Material and methods: The retrospective study included 20 prostate cancer patients treated with 40 Gy total dose over five fractions (8 Gy/fraction) using VMAT. Daily cone beam computed tomography images were acquired before the delivery of every fraction and then, with the application of deformable image registration used for the estimation of daily dose, contouring and plan re‐optimization. Dosimetric benefits of the various ART strategies were quantified by the comparison of dose and dose‐volume metrics derived from treatment planning objectives for original treatment plan and adapted plans with the consideration of target volumes (PTV and CTV) as well as critical structures (bladder, rectum, left, and right femoral heads). Results: Percentage difference (ΔD) between planning objectives and delivered dose in the D99% > 4000cGy (CTV) metric was −3.9% for the non‐ART plan and 2.1% to 4.1% for ART plans. For D99% > 3800cGy and Dmax < 4280cGy (PTV), ΔD was −11.2% and −6.5% for the non‐ART plan as well as −3.9% to −1.6% and −0.2% to 1.8% for ART plans, respectively. For D15% < 3200 cGy and D20% < 2800 cGy (bladder), ΔD was −62.4% and −68.8% for the non‐ART plan as well as −60.0% to −57.4% and −67.0% to −64.0% for ART plans. For D15% < 3200 cGy and D20% < 2800 cGy (rectum), ΔD was −11.4% and −8.15% for non‐ART plan as well as −14.9% to −9.0% and −11.8% to −5.1% for ART plans. Conclusions: Daily on‐line adaptation approaches were the most advantageous, although strategies adapting every other fraction were also impactful while reducing relative workload as well. Offline treatment adaptations were shown to be less beneficial due to increased dose delivered to bladder and rectum compared toother ART strategies.